Combined treatment of extranodular lymphoma localised in head and neck - Skowronek, Janusz; Nyczak, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2001)
Purpose : Lymphoma localized in head and neck region often has an individual course of disease different from lymphoma localized in other organs. In most of cases it’s only one of symptoms of disseminated disease. Patients are treated with different methods. Most often combined treatment comprising of chemotherapy, radiotherapy and sometimes surgery is recommended. In some cases surgical treatment is a treatment of choice. We present results of treatment of patients with extranodular lymphoma localized in head and neck region. Material and methods : 19 patients with head and neck lymphoma (11 women, 8 men) were treated between 1991 and 1999 in Greatpoland Cancer Center. Age of patients was from 17 to 74 years, average – 53,5. In 12 cases primary lesion was palatine tonsil, in 5 – nasopharynx and oropharynx, in 2 – maxillary sinus and nasal cavity. Lymphoma of low malignancy was diagnosed in 10 cases, in 4 cases – of high malignancy, in 2 cases – MALT lymphoma, in 2 cases – lymphoepithelioma, in 1 case – lymphoma of undifferentiated type. 5 patients were treated by surgery, radiotherapy and chemotherapy, 4 by surgery and radiotherapy, and 10 by radiotherapy and chemotherapy. In chemotherapy most often schema CHOP (14 patients) was used. Total doses of radiotherapy were from 20 to 60 Gy. Results : In 15 cases total remission was observed in first and third month after the end of treatment. In 2 cases – partial remission. In 2 cases progression was observed. 5 years survived 7 patients (36,8 proc.), 3 years survived 11 patients (57,9 proc.). Women tend to demonstrate longer free of disease survival then man – 44,2 versus 36 month. Conclusions : 1) patients with head and neck lymphoma need another treatment schema than patients with disseminated illness; 2) women tend to achieve longer free of disease survival time.